An analysis of cellulose‐ and dextrose‐based radicals in sweet potatoes as irradiation markers. Issue 9 (15th August 2020) - Tonyali, Bade; Sommers, Christopher; Ceric, Olgica; Smith, J. Scott; Yucel, Umut
Abstract : Abstract: Dried sweet potatoes (SPs) are often irradiated for improved safety and shelf life. Formation of irradiation‐derived radicals was analyzed using electron paramagnetic resonance (EPR) spectroscopy. These irradiation‐specific radicals can be used to characterize the irradiation history of dry plant‐based foods containing cellulose and sugars. The signal characteristics (intensity and peak shape) were evaluated at different sample locations (skin and flesh), as a function of sample preparation method (grinding, sieving, and pelletizing). The signal intensity was quantified using a double integration method of the peaks based on the area under the curve. The sieving caused ca. 50% decrease in total signal intensity as compared to nonsieved samples due to loss of cellulose‐based radicals. The flesh of irradiated SP showed complex EPR spectra with multiple satellite peaks of cellulose radicals (333.5 and 338.8 mT) and split peak of dextrose radicals (337.4 mT); while skin spectra were distinctive of cellulose radicals. In this study, we demonstrated the effects of sample composition and preparation method on formation and analysis of irradiation‐specific radicals based on EPR. Practical Application: In the last decade or so, there have been health concerns related to the consumption of irradiated pet food products. Electron paramagnetic resonance spectroscopy can be used to analyze the irradiation history of dry products containing cellulose and sugar, such as the popular dog treat dried sweet potatoes, to ensure the products were irradiated within safe limits. This work demonstrates that the formation of irradiation‐specific radicals is affected by the sample location (skin and flesh) and moisture content.